2017
DOI: 10.3389/fpsyg.2017.00730
|View full text |Cite
|
Sign up to set email alerts
|

The Positive and Negative Experiences of Caregiving for Siblings of Young People with First Episode Psychosis

Abstract: Background: The impact of first episode psychosis (FEP) upon parents’ experience of caregiving has been well-documented. However, the determinants and nature of this remain poorly understood in siblings. It is hypothesized that siblings of young people with FEP are also impacted by caregiving and burden. This study aimed to characterize the experience of caregiving for siblings of young people with FEP.Method: Survey methodology was used to explore the experience of 157 siblings in the first 18 months of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 79 publications
0
23
0
Order By: Relevance
“…In an Australian National Survey of Psychosis, 68% of participants had not finished high school (n = 1825; Waghorn et al, 2012). Recent studies with first episode psychosis (FEP) populations also indicate that over 50% have less than 10 years of education (Bowman, Alvarez‐Jimenez, Wade, Howie, & McGorry, 2017; Bowman, McKinstry, & McGorry, 2017). The pattern is also similar for other complex and potentially severe mental illnesses such as major mood disorders, anxiety disorders, eating disorders and borderline personality disorder with prospective international evidence (Australia, Canada, China, Finland, India, Mexica, Netherlands and New Zealand) demonstrating that 46% of school dropout is attributed to these disorders (Riglin, Frederickson, Shelton, & Rice, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In an Australian National Survey of Psychosis, 68% of participants had not finished high school (n = 1825; Waghorn et al, 2012). Recent studies with first episode psychosis (FEP) populations also indicate that over 50% have less than 10 years of education (Bowman, Alvarez‐Jimenez, Wade, Howie, & McGorry, 2017; Bowman, McKinstry, & McGorry, 2017). The pattern is also similar for other complex and potentially severe mental illnesses such as major mood disorders, anxiety disorders, eating disorders and borderline personality disorder with prospective international evidence (Australia, Canada, China, Finland, India, Mexica, Netherlands and New Zealand) demonstrating that 46% of school dropout is attributed to these disorders (Riglin, Frederickson, Shelton, & Rice, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The two studies in the current review that considered psychological wellbeing and the positive outcomes of care is indicative of the wider need to focus on this under-researched but developing area [ 30 , 31 , 120 ]. The two studies in this review were not consistent in their findings on psychological wellbeing, as one [ 71 ] found no difference between groups, while the other [ 59 ] noted that caregivers of those with schizophrenia reported higher positive, and paradoxically negative, caregiving experiences.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of literature that examines the experiences of siblings and, in particular, a lack of literature that explores the impact on siblings from a developmentally informed perspective (Bowman et al, 2015; Blinded for Review, 2016; Friedrich et al, 2008). Some studies have indicated that siblings can be sources of support to their parents, but may also experience significant amounts of stigma, caregiver burden, and distress (Bowman et al, 2017, Chan, 2016). Other studies have demonstrated that siblings of individuals with schizophrenia have a higher propensity to experience depressive symptoms (Smith et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%